2011
DOI: 10.1155/2011/185845
|View full text |Cite
|
Sign up to set email alerts
|

Inbuilt Mechanisms for Overcoming Functional Problems Inherent in Hepatic Microlobular Structure

Abstract: The spherical anatomy of human and rat liver lobules implies that more central cells have less time to carry out their function than more peripherally located cells because blood flows past them more rapidly. This problem could be overcome if more centrilobular cells could operate at higher temperatures than periportal cells. This study presents evidence for such a temperature gradient. Firstly, we use mathematical modelling to demonstrate that temperature increases towards the centre of the lobule. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…BMI was calculated as weight (kg)/height (m) 2 . The usage of alcohol was assessed by questionnaire (19).…”
Section: Measurement Of Clinical Parameters and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…BMI was calculated as weight (kg)/height (m) 2 . The usage of alcohol was assessed by questionnaire (19).…”
Section: Measurement Of Clinical Parameters and Variablesmentioning
confidence: 99%
“…Uncoupling protein 2 (UCP2) is a heat-generating mitochondrial inner-membrane carrier protein that is widely expressed in tissues including adipocytes (1) and liver micro-lobules (2). Although liver is the major site of UCP2 expression in the rodent foetus, the levels decline soon after birth (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failing to measure these rises by inserting fragile micro-thermocouples, he created a mathematical model of heat transfer down the radius of the lobule, which did show small increases. 12 Realising that the calculated heat differences would be insufficient, Cohen hypothesised that uncoupling proteins (UCP), notably UCP2, which prevent removal of energy from the electron transfer chain, might provide the explanation. Through immunohistochemistry studies on liver sections, Cohen and Boucher showed that UCP2 was indeed more highly concentrated at the centre of liver lobules in rats and humans.…”
Section: Obituariesmentioning
confidence: 99%
“…Cohen et al [34] also stated that the velocity near the CV is higher, resulting in a region of hepatocytes near the CV that have a much higher flux of blood passing them, as compared with hepatocytes that are located nearer the periphery. The flow patterns in the longitudinal sections through the PTs shown in Fig.…”
mentioning
confidence: 99%